Manifestations of lysosomal storage diseases in the stomatognathic system – a literature review - Machut, Katarzyna; Żółtowska, Agata (Journal of Stomatology, 2019)
The stomatognathic system comprises the mouth, teeth, jaws, pharynx, and related structures associated with mastication, swallowing, and speech. Lysosomal storage diseases (LSDs) are metabolic disorders, which cause an increase of systemic complication and are even life-threatening. They may also lead to a change in the socio-economic conditions of people suffering from these diseases, and their families. LSDs are inherited in an autosomal recessive pattern. Many syndromes of lysosomal diseases represent anomalies of the craniofacial region and in the oral cavity. For the vast majority, treatment is not required, but for some of them it is necessary to reconstruct the morphology or the proper function. The appearance of the face can have a negative impact on the quality of the patient’s life. Breathing, chewing, speaking, smiling, and mimic movements are the consequences of facial deformities. Irregularities of the sensory organs can sometimes be observed – especially of hearing, smell, and sight. The most frequent manifestations of lysosomal diseases in the oral cavity are malocclusion, macroglossia, tooth eruption, and development disorders as well as periodontal disorders, for instance hypertrophy of the gingiva. The population of people suffering from lysosomal diseases often have specific oral health needs compared to the population of generally healthy people.